International Legal Status of the Caspian Sea: Current Stage - I. I. Abdulaev (Проблемы постсоветского пространства, 2017)
This paper is devoted to the international legal status of the Caspian Sea. After the USSR breakup Iran and Russia were committed to the provisions of the Soviet-Iranian treaties and opposed the division of the Caspian Sea into national sectors. The new Caspian states had a different outlook: they supported the idea of the Caspian division into national sectors. They believed that the Russian-Persian and later on Russian-Iranian documents addressed the issues of fishery and navigationanddidnotregulatetheissues related to exploration, development and transit of hydrocarbons. This paper underlines that the active policy of the Caspian countries on the international legal status of the Caspian based on availability of hydrocarbon resources in the Caspian shelf.